Passive sampling monitoring of PAHs and trace metals in seawater during the salvaging of the Costa Concordia wreck (Parbuckling Project). (October 2018) - Schintu, Marco; Marrucci, Alessandro; Marras, Barbara; Atzori, Marco; Pellegrini, David
Abstract: Passive sampling techniques were used for monitoring trace metals and polycyclic aromatic hydrocarbons (PAHs) in the seawater surrounding the Costa Concordia shipwreck (Isola del Giglio, Italy). The monitoring lasted two and a half years (2012–2014) and considered all four phases of the "parbuckling project": stabilisation of the wreckage, installation of steel caissons on both sides of the wreck, parbuckling, and refloating. Dissolved trace metals (Cd, Cr, Cu, Hg, Ni, Pb, and V) were measured with diffusive gradients in thin films (DGT), while freely dissolved PAHs were measured with semi-permeable membrane devices (SPMDs). Passive sampling allowed to detect very low concentrations of contaminants, and indicated significant differences among the sampling stations and among the different steps for salvaging the wreck. The results suggested that the main source of contamination was the heavy working vessel traffic at the disaster site, rather than the release of contaminants from the wreck. Graphical abstract: Highlights: The largest parallel utilisation of passive samplers for both organics and metals to date Detection of dissolved PAHs and trace metals in seawater far below the limits established by EU legislation Vanadium as indicator of oil pollution in seawater